Independent and Combined Effects of Antioxidant Supplementation and Circuit Resistance Training on Selected Adipokines in Postmenopausal Women - Ayoub Saeidi (17331085) (2019)
We examined the effects of the independent and combined effects of Zataria Multiflora supplementation and circuit resistance training (CRT) on selected adipokines among postmenopausal women. Forty-eight postmenopausal women were divided into four groups: Exercise (EG, n = 12), Zataria Multiflora (ZMG, n = 12), exercise and Zataria Multiflora (ZMEG, n = 12), and control (CG, n = 12). Participants in experimental groups either performed CRT (3 sessions per week with intensity at 55% of one-repetition maximum) or supplemented with Zataria Multiflora (500 mg every day after breakfast with 100 ml of water), or their combination, for 8 weeks. Blood samples were collected at pre- and post-intervention for measuring selected adipokines, including visfatin, omentin-1, vaspin, FGF-21, adiponectin, leptin, and ghrelin. Our findings demonstrated that visfatin, vaspin, and leptin levels significantly decreased over the intervention period (all p < 0.05), with these values were lower in EG and ZMEG in comparison to CG at post-intervention (all p < 0.05). Visfatin and vaspin levels were also lower in ZMEG in comparison to EG at post-intervention (both p < 0.05). In contrast, omentin-1, ghrelin, adiponectin, and FGF21 significantly increased in EG and EMG (all p < 0.05) after CRT. These findings suggest that Zataria Multiflora supplementation by itself has little effect on measured adipokines; however, its combination with CRT produced noticeable effects on circulating levels of these adipokines, even more than CRT alone. Consequently, a combination of CRT and Zataria Multiflora supplementation may represent a potentially beneficial non-pharmacologic intervention on some selected adipokines in postmenopausal women. Other Information Published in: Frontiers in Physiology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fphys.2019.00484